Pengaruh Citra Merek dan Ulasan Pelanggan terhadap Kepercayaan Konsumen Shopee di Medan Johor - Rexsy Mardohot Sitanggang; Adelina Lubis; Aprinawati; Karolin Gabrela Sitanggang (Universitas Muhammadiyah Palembang, 2025)
Purpose – This study aims to analyze the effect of brand image and customer reviews on consumer trust in the Shopee marketplace in Medan Johor District. Design/methodology – This research employs a quantitative approach using a survey method. Data were collected through a questionnaire distributed to 100 respondents who had shopped on Shopee. The methodology includes validity and reliability tests, classical assumption tests (normality, multicollinearity, heteroscedasticity), and hypothesis testing using t-tests and F-tests. Data analysis was conducted using multiple linear regression with the aid of SPSS. Findings - The results indicate that brand image has a positive and significant effect on consumer trust (p = 0.001). Similarly, customer reviews significantly influence consumer trust (p = 0.002). Both factors together account for a significant portion of the variance in consumer trust, emphasizing their critical role in shaping consumer perceptions.